Taxonomy in the electronic age and an e‐monograph of the papaya family (Caricaceae) as an example. (13th August 2014) - Antunes Carvalho, Fernanda; Filer, Denis; Renner, Susanne S.
Abstract The need for taxonomists to take full advantage of biodiversity informatics has been clear for at least 10 years. Significant progress has been made in providing access to taxonomic resources online, including images of specimens (especially types), original species descriptions, and georeferenced collection data. However, in spite of persuasive calls for e‐monography, there are few, if any, completed project, even though monographic research is the only mechanism for reducing synonymous names, which are estimated to comprise 50% of all published names. Caricaceae is an economically important family of flowering plants from Africa and the Neotropics, best known for the fruit crop papaya. There is a large amount of information on the family, especially on chemistry, crop improvement, genomics, and the sex chromosomes of papaya, but up‐to‐date information on the 230 names and which species they might belong to was not available. A dynamically updated e‐monograph of the Caricaceae now brings together all information on this family, including keys, species descriptions, and specimen data relating the 230 names to 34 species and one hybrid. This may be the first taxonomic monograph of a plant family completely published online. The curated information will be continuously updated to improve the monograph's comprehensiveness and utility.